ANALISIS BIBLIOMETRIK TENTANG RISET STRATEGI PEMASARAN BANK SYARIAH - Lukmanul Hakim; Fenny Mei Angraeni (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2022)
The marketing of Islamic banks has become an interesting topic in recentdecades, along with the development of the halal industry in various countries. It isnormal that there is a lot going on about the absence of conventions amongacademics. This is natural because they also experience other disciplines such asthe study of innovation, information systems, and entrepreneurship which are stillin the stage of scientific development. The purpose of this study is to review thestrategies carried out by Islamic banks by providing extensive bibliometric analysisto answer research or in bibliometric terms called RQ. RQ1 Shows research trendson Islamic Bank Marketing based on the number of articles per year, RQ2 researchTop 10 peer-reviewed journals with the most publications, RQ3 top article authorsfrom peer-reviewed published articles and Hussainey K has been the mostproductive, RQ4 is a publication in the field that comes from several other subjectsand disciplines, RQ5 main topics and research in the field visualizing the networkdescribing 8 clusters, RQ6 topics topics for the future, RQ7 this author's countrywhich provides the most publications and collaboration between authors, and RQ8of the most influential articles based on citations in research.